Valuable Guidelines for the Formation and Development of Personality Hardiness - Dmytro Kostenko (Pedagogical Discourse, 2023)
The article examines the value orientations of the formation and development of the hardiness of the individual. An analysis of modern socialization challenges is presented. The value orientations of higher education students in the educational environment of the university are accented. The value orientations of the formation and development of the hardiness of the individual are considered. The priority values ​​of higher education students in the conditions of modern socialization challenges are highlighted.The tasks include the definition of modern socialization challenges, theoretical analysis of scientific works of domestic and foreign authors regarding the terminology of the main concepts of the article, highlighting the priority of value guidelines for the formation and development of the hardiness of higher education students in the educational environment of the university. The article uses theoretical methods: analysis of philosophical, psychological-pedagogical, socio-pedagogical, and sociological literature to present the main theoretical principles of the problem under study; comparison and generalization for the systematization of scientific positions of domestic and foreign scientists; assessment of the resources of the innovative educational environment to determine the priority value orientations of higher education students in the conditions of modern socialization challenges.A theoretical analysis of the scientific works of domestic and foreign authors regarding the concepts of «value», «value orientations» was carried out.